PENGARUH BIOCHAR TEMPURUNG KELAPA DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI MENTIMUN (Cucumis sativus L.) PADA TANAH PODZOLIK MERAH KUNING - Dimas Yudistira; Sulhaswardi (DINAMIKA PERTANIAN, 2025)
This research aims to determine the main and interaction effects of Coconut Shell Biochar and Cow Manure on the growth and production of cucumbers (Cucumis sativus L.) on red and yellow podzolic soil. The research was conducted at the Cold Water Experimental Farm, Faculty of Agriculture, Riau Islamic University, Pekanbaru City, for 3 months, from May to July 2023. This research used a Factorial Completely Randomized Design (CRD) consisting of two factors. The first factor is Coconut Shell Biochar (B), which consists of 5 levels, namely 0, 830, 1,660, 2,500, and 3,330 g/plot, and the second factor is Cow Manure (S), consisting of 4 levels, namely 0, 500, 1,000, and 1,500 g/plot, to obtain 20 treatment combinations with 3 replications, so there are 60 experimental units. The parameters observed were flowering age, male-to-female flower ratio, harvest age, number of fruit per plant, fruit weight per plant, fruit weight per fruit, and fruit length per fruit. The observation data were analyzed statistically, and the BNJ test was performed at the 5% level. The research results showed that the interaction between Coconut Shell Biochar and Cow Manure had a significant effect on the parameters of harvest age, male-to-female flower ratio, fruit weight per plant, fruit weight per fruit, and fruit length per fruit. The best combination was Coconut Shell Biochar at a dose of 3,330 g/plot and Cow Manure at a dose of 1,500 g/plot. The main effects of Coconut Shell Biochar and Cow Manure were significant on all observed parameters. The best treatment is Coconut Shell Biochar at a dose of 3,330 g/plot and Cow Manure at a dose of 1,500 g/plot.